Lightweight sandwich structure with flame retardant properties and method for making same

A lightweight, flame-retardant composite structure is achieved by using a thermoplastic foam core with an adhesive film of lower glass transition temperature, bonded at lower pressures and temperatures, addressing the challenge of core distortion and ensuring strong adhesion and efficient production.

JP7625534B2Active Publication Date: 2025-02-03CYTEC IND INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021560866
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-17
Filing Date
2020-04-17
Publication Date
2025-02-03
Estimated Expiration
2040-04-17

AI Technical Summary

Technical Problem

The assembly of a multi-layered composite structure with a thermoplastic foam core is challenging due to the need for high temperature and pressure, which can cause core collapse or distortion, making it difficult to achieve a strong bond between the core and outer skin layers.

Method used

A lightweight, flame-retardant multi-layered composite structure is created using a thermoplastic foam core with an adhesive film, where the adhesive film has a lower glass transition temperature than the foam core, allowing for bonding at lower pressures and temperatures, using a continuous double belt process without external heat sources.

Benefits of technology

This method ensures a strong adhesive bond between the foam core and outer skin layers, maintaining the integrity of the foam core while meeting flame-retardant standards, with improved production speed and reduced risk of distortion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625534000014
    Figure 0007625534000014
  • Figure 0007625534000015
    Figure 0007625534000015
  • Figure 0007625534000016
    Figure 0007625534000016
Patent Text Reader

Abstract

A lightweight, flame-retardant, multi-layer composite structure having at least the following components: a thermoplastic foam core having two opposing surfaces, a thermoplastic adhesive film on at least one of the opposing surfaces of the foam core, and one or more composite layers in each adhesive film. The composite layers are composed of reinforcing fibers embedded in a thermoplastic polymer or thermosetting resin matrix. The adhesive bond is achieved by interleaved thermoplastic adhesive films inserted between the thermoplastic foam core and adjacent composite layers. The thermoplastic adhesive films are preferably interleaved with the foam core material. g At least 20°C lower than T g The thermoplastic polymer composition has the following structure:
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE This disclosure relates generally to lightweight composite materials having thermoplastic foam layers, their applications, and methods for assembling such structures. [Brief description of the drawings]

[0002] [Figure 1] 1 illustrates an exemplary sandwich structure with a thermoplastic foam core. [Diagram 2] 1 illustrates an exemplary apparatus with a double-belt press system for producing sandwich structures. [Diagram 3] 1 shows a polished image of an interface of a control sandwich panel taken at 100x magnification in dark field light, the control sandwich panel being manufactured according to Example 1 disclosed herein. [Figure 4] 1 shows a finished image of the interface of another sandwich panel taken at 100x magnification in dark field light, the other sandwich panel being manufactured according to Example 2 disclosed herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0003] Composite sandwich structures with thermoplastic foam cores have been used in aircraft interior structures such as cabin door and wall panels. Such sandwich structures provide strength and rigidity while minimizing the weight of the structure. Although aircraft interior composite parts do not require the structural performance of primary structures such as fuselages and wings, they still have their own stringent requirements, including rigidity and strength at low weight, dimensional stability, durable aesthetics, chemical resistance to cleaning solvents, and stringent flame retardant standards for flame, smoke and toxicity (FST) and heat release rate (HRR) standards.

[0004] The assembly of multi-layer composite structures composed of thermoplastic materials is difficult because of the high temperatures and pressures required to ensure good bonding of the various thermoplastic layers. One challenge presented by the manufacture of sandwich structures having a thermoplastic foam core between outer skin layers is the ability to obtain good bonding between the core and skin layers without the use of high consolidation pressures that would collapse the foam core.

[0005] In the conventional process of bonding a honeycomb or foam core to an outer skin layer, the entire sandwich panel assembly is advanced through a heating zone, which heats the panel to a bonding temperature, typically under pressure applied by heated press platens. When a thermoplastic core is used, the temperature required for bonding is typically above the glass transition temperature (T g ), and pressure is too high, collapse or distortion of the core occurs. Such collapse or distortion is due to a combination of excessive heat transfer from the press platens through the outer skin to the core, and thus the temperature of the foamed core exceeds the T of the thermoplastic core material. g , and the pressure applied by the press platens increases.

[0006] One aspect of the present disclosure relates to a lightweight, flame retardant, multi-layer composite structure having at least the following components: a thermoplastic foam core having two opposing surfaces, a thermoplastic adhesive film on at least one of the opposing surfaces of the foam core, and one or more composite layers on each adhesive film. The adhesive bond is achieved by interleaving thermoplastic adhesive films inserted between the thermoplastic foam core and adjacent composite layers. The composite layers are composed of reinforcing fibers embedded in a thermoplastic polymer or thermoset matrix. The thermoplastic foam core has a glass transition temperature (T g ) is formed from a foamed thermoplastic material having a temperature of at least 200°C, preferably 210°C to 240°C, and the thermoplastic adhesive film is formed from a foamed thermoplastic material having a temperature of at least 200°C, preferably 210°C to 240°C. g At least 20°C lower than T g The thermoplastic polymer composition has the following structure:

[0007] In a preferred embodiment, the multi-layer composite structure is a sandwich structure in which the thermoplastic foam core is inserted in sheet form between two outer skins. Figure 1 shows an exemplary sandwich structure including a thermoplastic foam core 10, alternating adhesive films 11A and 11B, and outer skins 12A and 12B, where each outer skin is composed of a laminate of multiple composite layers or a single composite layer. The composite layers of the skins can be the same as each other or different. Furthermore, the thermoplastic foam core is free of any reinforcing fibers, such as carbon, glass, and polymer fibers, or any openings extending through its thickness.

[0008] In a preferred embodiment, the foam core and skin materials of the sandwich structure are selected so that the sandwich structure complies with the flammability requirements for materials in FAR / JAR / CS 23.853 "Passenger and crew compartment interiors" and 23.855 "Cargo and baggage compartment fire protection."

[0009] The selected thermoplastic adhesive used to bond the thermoplastic foam core to the composite layer provides an excellent bond in terms of fracture toughness and peel strength of the bond. Furthermore, it has been discovered that the use of an adhesive thermoplastic film with a glass transition temperature about 20°C lower than the foam core material provides a sandwich structure that is compatible with a continuous low pressure double belt process, allowing for high production rates. Compared to conventional methods that require an external heat source during lamination, the double belt process does not require such an external heat source to melt the interleaved adhesive layers between the skins and the thermoplastic foam core. The heat transferred through the belt and skin material to the underlying adhesive film is sufficient to melt the adhesive film without causing distortion of the skins or collapse of the foam core.

[0010] Thermoplastic Foam Core In the context of the present disclosure, the term "foam" is used in the sense commonly known to those skilled in the art. With reference to IUPAC, Compendium of Chemical Terminology, 2nd ed. (the "Gold Book" Compiled by A.D. McNaught and A. Wilkinson. Blackwell Scientific Publications, Oxford 1997, XML on-line corrected version: http: / / goldbook.iupac.org(2006)created by M.Nic, J.Jirat, B.Kosata; updates compiled by A.Jenkins. ISBN 0-9678550-9-8.doi:10.1351 / goldbook), the term "foam" refers to a dispersion state in which a large proportion of gas by volume is dispersed in a liquid, solid, or gel in the form of bubbles. The diameter of the bubbles is usually larger than 1 μm, while the thickness of the lamellae between the bubbles is often in the range of normal colloidal sizes.

[0011] As a non-limiting example, at least 50% of the volume of a foamed thermoplastic material according to the present disclosure can be occupied by gas, e.g., at least 60%, at least 70%, at least 80%, or at least 90%, based on the total volume of the composition.

[0012] Foam core: 20~1000kg / m 3 , 30~800kg / m 3 , 35~500kg / m 3 , 40~300kg / m 3 , or 45 to 200 kg / m 3 In a preferred embodiment, the foam core may have a density of 45 to 150 kg / m 3 , more preferably 45 to 80 kg / m 3 The density can be measured according to ASTM D1622.

[0013] According to one embodiment, the foam core has an average cell size of less than 1000 μm, less than 500 μm, less than 300 μm, or less than 250 μm. Cell size can be measured using optical or scanning electron microscopy.

[0014] The foam core may have a thickness ranging from 3 mm to 50 mm, and in some embodiments, from 5 mm to 25 mm.

[0015] The foam core of the multilayer composite structure disclosed herein is formed from a foamable composition comprising at least one polymer selected from poly(aryl ether sulfone) (PAES), particularly polyether sulfone (PES), polyether ether sulfone (PEES), poly(biphenyl ether sulfone) (PPSU), polyamide (PA), polyimide (PI), polyetherimide (PEI), and copolymers thereof. Generally, the foam core has a T in the range of 201° C. to 290° C. g PAES polymers having the following properties are suitable for the purposes disclosed herein. In some embodiments, the foamable composition includes a combination of various thermoplastic polymers. The T between various PAES polymers g The difference is due to the difference in the backbone structure of the polymer.

[0016] For purposes of this disclosure, a “poly(aryl ether sulfone) (PAES)” is a poly(aryl ether sulfone) having at least 50 mol % of repeat units of formula (K): PAES ), where mole % is based on the total moles of repeat units in the polymer: [ka] (In the formula, R is independently selected at each occurrence from the group consisting of halogen, alkyl, alkenyl, alkynyl, aryl, ether, thioether, carboxylic acid, ester, amide, imide, alkali or alkaline earth metal sulfonate, alkyl sulfonate, alkali or alkaline earth metal phosphonate, alkyl phosphonate, amine, and quaternary ammonium; h is, independently for each R, zero or an integer ranging from 1 to 4; T is a bond, a sulfone group [-S(=O) 2 ], and the group -C(R j )(R k )-(in this case, R j and R k are equal to or different from each other and are selected from the group consisting of hydrogen, halogen, alkyl, alkenyl, alkynyl, ether, thioether, carboxylic acid, ester, amide, imide, alkali or alkaline earth metal sulfonate, alkyl sulfonate, alkali or alkaline earth metal phosphonate, alkyl phosphonate, amine, and quaternary ammonium).

[0017] T is preferably a bond, a sulfone group or a group -C(R j )(R k )-(wherein, R j and R k is preferably a methyl group.

[0018] Poly(biphenyl ether sulfone) (PPSU) is particularly suitable as a foam core material. For purposes of this disclosure, poly(biphenyl ether sulfone) polymer (PPSU) is defined as a polymer having at least 50 mol % of repeat units (R PPSU ), where mole % is based on the total moles in the polymer: [ka] (In the formula, R is independently selected at each occurrence from the group consisting of halogen, alkyl, alkenyl, alkynyl, aryl, ether, thioether, carboxylic acid, ester, amide, imide, alkali or alkaline earth metal sulfonate, alkyl sulfonate, alkali or alkaline earth metal phosphonate, alkyl phosphonate, amine, and quaternary ammonium; h, for each R, is independently zero or an integer ranging from 1 to 4 (e.g., 1, 2, 3, or 4).

[0019] According to one embodiment, R is independently selected at each position in formula (K) above from the group consisting of C1-C12 moieties optionally containing one or more heteroatoms, sulfonic acid and sulfonate groups, phosphonic acid and phosphonate groups, amines, and quaternary ammonium groups.

[0020] According to one embodiment, h is zero for each R. In other words, according to this embodiment, the repeating unit (R PPSU ) is represented by the formula (K'): [ka] is a unit of.

[0021] According to one embodiment, at least 60 mol%, at least 70 mol%, at least 80 mol%, at least 90 mol%, at least 95 mol%, at least 99 mol%, or all of the repeat units of the PPSU are repeat units of formula (K) and / or formula (K′) (R PPSU ).

[0022] According to one embodiment, the PPSU polymer has formula (L): [ka] (mol % is based on the total number of moles in the polymer) PPSU ).

[0023] The PPSU polymer of the present disclosure may therefore be a homopolymer or a copolymer. If it is a copolymer, it may be a random, alternating or block copolymer.

[0024] According to a preferred embodiment, at least 60 mol%, at least 70 mol%, at least 80 mol%, at least 90 mol%, at least 95 mol%, at least 99 mol%, or all of the repeat units of the PPSU are repeat units of formula (L) (R PPSU ).

[0025] When the PPSU is a copolymer, the repeating units thereof are the repeating units (R PPSU ) and the following formula (M), (N) and / or (O): [ka] (In the formula, R is independently selected at each occurrence from halogen, alkyl, alkenyl, alkynyl, aryl, ether, thioether, carboxylic acid, ester, amide, imide, alkali or alkaline earth metal sulfonate, alkyl sulfonate, alkali or alkaline earth metal phosphonate, alkyl phosphonate, amine, and quaternary ammonium; i is, for each R, independently, zero or an integer ranging from 1 to 4 (e.g., 1, 2, 3, or 4), PPSU It is a mixture of repeating units (R*) different from those mentioned above.

[0026] According to one embodiment, R is, at each position in the above formulas (M)-(O), independently selected from the group consisting of C1-C12 moieties optionally containing one or more heteroatoms, sulfonic acid and sulfonate groups, phosphonic acid and phosphonate groups, amines, and quaternary ammonium groups.

[0027] According to one embodiment, for each R of formula (M), (N) or (O), i is zero and the repeat unit R* is of the following formula (M'), (N') and (O'): [ka] is selected from.

[0028] According to some embodiments, less than 40 mol%, less than 30 mol%, less than 20 mol%, less than 10 mol%, less than 5 mol%, less than 1 mol%, or all of the repeat units of the PPSU are repeat units of formula (M), (N), (O), (M'), (N'), and / or (O').

[0029] According to one embodiment, the PPSU comprises the repeating unit (R PPSU ) and R PPSU and a repeat unit (R*) different from the repeat unit (M"), where R* is a copolymer of the following formulae (M"), (N"), and (O"): [ka] is selected from.

[0030] According to some embodiments, less than 45 mol%, less than 40 mol%, less than 35 mol%, less than 30 mol%, less than 20 mol%, less than 10 mol%, less than 5 mol%, less than 1 mol%, or all of the repeat units of the PPSU are repeat units of formula (M"), (N"), and / or (O").

[0031] PPSU for purposes herein may be a blend of a PPSU homopolymer and at least one PPSU copolymer, as described above.

[0032] The PPSU polymer disclosed herein can be prepared by any method known in the art. As an example, the PPSU polymer mat can be the result of the condensation of 4,4'-dihydroxy-biphenyl (biphenol) with 4,4'-dichlorodiphenyl sulfone. The reaction of the monomer units occurs by nucleophilic aromatic substitution with the elimination of one unit of hydrogen halide as the leaving group. However, it should be noted that the structure of the resulting poly(biphenyl ether sulfone) does not depend on the nature of the leaving group.

[0033] Defects, end groups and monomeric impurities may be incorporated into the (co)polymer (PPSU) of the present disclosure in very small amounts, advantageously without adversely affecting its performance.

[0034] An example of a PPSU suitable for the purposes disclosed herein is Radel® PPSU, available from Solvay Specialty Polymers USA, LLC.

[0035] In a preferred embodiment, the thermoplastic foamed core has a T range of 210°C to 240°C. g and formed from a foamable composition comprising poly(biphenyl ether sulfone) polymer (PPSU) as a major component, i.e., the PPSU is present in an amount greater than 50 wt.% (weight percent), or greater than 80 wt.%, based on the total weight of the composition. The weight average molecular weight (Mw) of the PPSU can be from 30,000 to 90,000 g / mol, e.g., from 40,000 to 80,000 g / mol, or from 50,000 to 70,000 g / mol.

[0036] The weight average molecular weight (Mw) of PAES, including PPSU and PSU, can be determined by gel permeation chromatography (GPC) using methylene chloride as the mobile phase (2×5μ mixed D column with guard column from Agilent Technologies, flow rate: 1.5 mL / min, injection volume: 20 μL of 0.2 w / v% sample solution) with polystyrene standards.

[0037] More precisely, the weight average molecular weight (Mw) of PAES polymers can be measured by gel permeation chromatography (GPC), using methylene chloride as the mobile phase. For example, the following detailed method can be used: For separation, two 5μ mixed D columns with guard columns from Agilent Technologies are used. A UV detector at 254 nm is used to obtain the chromatograms. A flow rate of 1.5 mL / min and an injection volume of 20 μL of a 0.2 w / v% solution in the mobile phase are selected. Calibration is performed using 12 narrow molecular weight polystyrene standards (peak molecular weight range: 371,000-580 g / mol).

[0038] In addition to the above thermoplastic polymer, e.g., PAES, the foamable composition for forming the foam core may further comprise up to 10 wt. % of at least one additive (AD), based on the total weight of the polymer composition. The additives may be selected from the following: nucleating agents, chemical blowing agents or their residues, stabilizers such as UV absorbers, light stabilizers, etc., lubricants, plasticizers, pigments, dyes, colorants, antistatic agents, metal deactivators, and mixtures thereof.

[0039] Examples of antioxidants are phosphites, phosphorates, hindered phenols or mixtures thereof. Surfactants may also be added to help nucleate cells and stabilize them during the bubble growth phase of the foaming process.

[0040] In some embodiments, the foamable composition includes one or more nucleating agents. Nucleating agents help control the foam structure by providing sites for bubble formation. Examples of nucleating agents are glass fiber, carbon fiber, graphite fiber, silicon carbide fiber, aramid fiber, wollastonite, talc, mica, clay, calcium carbonate, titanium dioxide, potassium titanate, silica, silicates, kaolin, chalk, alumina, aluminates, boron nitride, and aluminum oxide.

[0041] The foamable composition may further comprise one or more inorganic pigments. Inorganic pigments are added to obtain the selected appearance of the composition by changing the color of reflected or transmitted light as a result of wavelength-selective absorption. Examples of inorganic pigments are titanium dioxide, zinc sulfide, zinc oxide, magnesium oxide, barium sulfate, carbon black, cobalt phosphate, cobalt titanate, cadmium sulfoselenide, cadmium selenide, copper phthalocyanine, ultramarine, ultramarine violet, zinc ferrite, magnesium ferrite, and iron oxide.

[0042] The foamable composition may comprise 0.1-9 wt%, 0.2-5 wt%, or 0.5-2 wt% of at least one additive (AD) based on the total weight of the composition. According to one embodiment, the foamable composition comprises 0.1-9 wt%, 0.2-5 wt%, or 0.5-3 wt% of at least one nucleating agent based on the total weight of the composition.

[0043] The foaming process may be a chemical foaming process or a physical foaming process. When the foaming process is a chemical foaming process, a chemical foaming agent, in particular a chemical expansion agent, may be used. A chemical foaming agent generally refers to a composition that decomposes or reacts under the influence of heat at foaming conditions to generate a foaming gas. A chemical foaming agent may be added to a polymer composition to generate a foaming gas in situ. Chemical foaming may also be achieved in an extrusion device.

[0044] Thermoplastic Adhesive In some embodiments, the thermoplastic adhesive films disclosed herein for bonding purposes have a T of less than 200° C., for example, based on the total weight of the film. g The adhesive film may have a thickness in the range of 25 to 250 microns (μm), e.g., in the range of 30 to 220 μm or in the range of 35 to 200 μm.

[0045] A preferred polysulfone (PSU) has the following formula (U): [ka] (mol % is based on the total moles of repeat units in the polymer) PSU ) at least 50 mol % of the repeat units.

[0046] According to one embodiment, at least 60 mol % (based on the total moles of repeat units in the polymer), at least 70 mol %, at least 80 mol %, at least 90 mol %, at least 95 mol %, at least 99 mol %, or all of the repeat units of the PSU are repeat units of formula (U) (R PSU ).

[0047] The PSU polymer can be a homopolymer or a copolymer. If the PSU polymer is a copolymer, it can be a random, alternating or block copolymer.

[0048] When the polysulfone (PSU) is a copolymer, it has the formula (M), (N) and / or (O): [ka] Repeating units (R PSU ) and the repeating unit (R PSU ), plus the repeat unit (R A ).

[0049] A suitable commercially available PSU is Udel® PSU from Solvay Specialty Polymers USA, LLC.

[0050] In a preferred embodiment, the adhesive film is a PSU polymer in which 80% to 100%, or at least 90 mol %, or all of the repeat units are repeat units of formula (U) (R PSU ) and T of 180°C to 190°C, preferably about 185°C. g The PSU polymer has the formula:

[0051] Weight average molecular weight of PSU (M w ) may be from 30,000 to 110,000 g / mol, for example, from 40,000 to 100,000 g / mol or from 50,000 to 90,000 g / mol, as determined by GPC as described above.

[0052] Polysulfone polymers can be made by various methods. For example, US Patent No. 4,108,837 and US Patent No. 4,175,175 describe the preparation of polyarylethers, particularly polyarylethersulfones. Several one-step and two-step processes are described in these patents, which are incorporated herein by reference in their entirety. In these processes, a double alkali metal salt of a dihydric phenol is reacted with a dihalobenzene compound in the presence of a sulfone or sulfoxide solvent under substantially anhydrous conditions. In the two-step process, the dihydric phenol is first converted in situ to an alkali metal salt derivative in the presence of a sulfone or sulfoxide solvent by reaction with an alkali metal or an alkali metal compound. In the case of PSU production, the starting monomers are bisphenol A and 4,4'-dihalodiphenylsulfone, typically 4,4'-dichlorodiphenylsulfone. Bisphenol A is first converted to its di-alkali metal salt derivative by reacting with a base such as sodium hydroxide, NaOH, in a 1:2 stoichiometric molar ratio to produce the disodium salt of bisphenol A. This disodium salt of bisphenol A is then reacted with 4,4'-dichlorodiphenyl sulfone in a second step to produce the polymer. The sodium chloride salt is produced as a by-product of the polymerization.

[0053] composite layer In some embodiments, the composite layers of the multi-layer composite structure include reinforcing fibers embedded in a thermoplastic polymer matrix.

[0054] As used in this disclosure, the term "embedded" means firmly fixed in the surrounding mass, and the term "matrix" means a mass of material, e.g., a polymer, in which something is encapsulated or embedded.

[0055] The thermoplastic polymer matrix comprises one or more thermoplastic polymers, which may be amorphous or semi-crystalline. The thermoplastic polymers as a whole constitute the majority component of the polymer matrix, or more than 50% by weight of the polymer matrix, for example 80-100% by weight, is composed of thermoplastic polymers. Suitable thermoplastic polymers include, but are not limited to, poly(arylethersulfone) (PAES), particularly polyethersulfone (PES), polyetherethersulfone (PEES), poly(biphenylethersulfone) (PPSU), polyamide (PA), polyimide (PI), polyetherimide (PEI), poly(aryletherketone) (PAEK) polymers such as polyetherketoneketone (PEKK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyphthalamide (PPA), thermoplastic polyurethane, poly(methylmethacrylate) (PMMA), polyphenylene sulfide (PPS), polyphenylene oxide (PPO), and copolymers thereof.

[0056] Generally, T ranges from 201℃ to 290℃. g PAES polymers having the formula: are suitable for the purposes disclosed herein. In some embodiments, the thermoplastic polymer matrix comprises more than 50 wt. % of the PPSU polymer described above with respect to the foamed thermoplastic material, e.g., 80-100 wt. %.

[0057] In another embodiment, the composite layer comprises reinforcing fibers embedded in a thermosetting resin matrix that hardens upon thermal curing. Preferably, the thermosetting resin matrix comprises at least one epoxy resin, preferably a blend of different epoxy resins, and at least one hardener. The epoxy resin and hardener together constitute more than 50% by weight of the thermosetting resin matrix, for example, between 60% and 100% by weight.

[0058] Suitable epoxy resins include polyglycidyl derivatives of aromatic diamines, aromatic monoprimary amines, aminophenols, polyhydric phenols, polyhydric alcohols, polycarboxylic acids. Examples of suitable epoxy resins include polyglycidyl ethers of bisphenols, such as bisphenol A, bisphenol F, bisphenol C, bisphenol S and bisphenol K, and polyglycidyl ethers of cresols and phenolic novolacs.

[0059] Specific examples are the tetraglycidyl derivative of 4,4'-diaminodiphenylmethane (TGDDM), resorcinol diglycidyl ether, triglycidyl-p-aminophenol, triglycidyl-m-aminophenol, bromobisphenol F diglycidyl ether, the tetraglycidyl derivative of diaminodiphenylmethane, trihydroxyphenylmethane triglycidyl ether, polyglycidyl ether of phenol-formaldehyde novolac, polyglycidyl ether of o-cresol novolac or the tetraglycidyl ether of tetraphenylethane.

[0060] Commercially available epoxy resins include N,N,N',N'-tetraglycidyldiaminodiphenylmethane (e.g., MY9663, MY720, and MY721 from Huntsman), N,N,N',N'-tetraglycidyl-bis(4-aminophenyl)-1,4-diisopropylbenzene (e.g., EPON 1071 from Momentive), N,N,N',N'-tetraclycidyl-bis(4-amino-3,5-dimethylphenyl)-1,4-diisopropylbenzene (e.g., EPON 1072 from Momentive), triglycidyl ethers of p-aminophenol (e.g., MY9663, MY720, and MY721 from Huntsman), and N,N,N',N'-tetraglycidyl-bis(4-aminophenyl)-1,4-diisopropylbenzene (e.g., EPON 1072 from Momentive). 0510), triglycidyl ethers of m-aminophenol (e.g. MY0610 from Hunstman), diglycidyl ethers of bisphenol A based materials such as 2,2-bis(4,4'-dihydroxyphenyl)propane (e.g. DER661 from Dow, or EPON 828 from Momentive, and preferably novolak resins having a viscosity of 8-20 Pa·s at 25°C, glycidyl ethers of phenol novolak resins (e.g. DEN431 or DEN438 from Dow), di-cyclopentadiene based phenol novolaks (e.g. Tactix 556 from Huntsman), diglycidyl 1,2-phthalate (e.g. GLY CEL A-100), diglycidyl derivatives of dihydroxydiphenylmethane (bisphenol F) (e.g., Huntsman's PY306). Other suitable epoxy resins include alicyclic compounds such as 3',4'-epoxycyclohexyl-3,4-epoxycyclohexanecarboxylate (e.g., Huntsman's CY179).

[0061] The curing agent is suitably selected from known curing agents, such as aromatic or aliphatic amines, or guanidine derivatives.Specific examples are 3,3'- and 4-,4'-diaminodiphenylsulfone (DDS), methylenedianiline, bis(4-amino-3,5-dimethylphenyl)-1,4-diisopropylbenzene, bis(4-aminophenyl)-1,4-diisopropylbenzene, 4,4'methylenebis-(2,6-diethyl)-aniline (MDEA from Lonza), 4,4'methylenebis-(3-chloro,2,6-diethyl)-aniline (MCDEA from Lonza), 4,4'methylenebis -(2,6-diisopropyl)-aniline (M-DIPA from Lonza), 3,5-diethyltoluene-2,4 / 2,6-diamine (D-ETDA80 from Lonza), 4,4'methylenebis-(2-isopropyl-6-methyl)-aniline (M-MIPA from Lonza), 4-chlorophenyl-N,N-dimethylurea (e.g. Monuron), 3,4-dichlorophenyl-N,N-dimethylurea (e.g. Diuron) and dicyanodiamide (e.g. AMICURE® CG1200 from Pacific Anchor Chemical).

[0062] The thermosetting resin matrix may further contain other additives such as catalysts, comonomers, rheology control agents, tackifiers, inorganic or organic fillers, thermoplastic and / or elastomeric polymers as reinforcing agents, core-sheath rubber particles, UV stabilizers / additives, viscosity modifiers / flow control agents, stabilizers, inhibitors, pigments, dyes, flame retardants, reactive diluents, and other additives known to those skilled in the art to modify the properties of the matrix resin before or after curing.

[0063] Suitable toughening agents for the thermoset matrix include, but are not limited to, homopolymers or copolymers of polyamides, copolyamides, polyimides, aramids, polyketones, polyetherimides (PEI), polyetherketones (PEK), polyetherketoneketones (PEKK), polyetheretherketones (PEEK), polyethersulfones (PES), polyetherethersulfones (PEES), polyesters, polyurethanes, polysulfones, polysulfides, polyphenylene oxides (PPOs) and modified PPOs, poly(ethylene oxide) (PEOs) and polypropylene oxides, polystyrenes, polybutadienes, polyacrylates, polymethacrylates, polyacrylics, polyphenylsulfones, high performance hydrocarbon polymers, liquid crystal polymers, elastomers and segmented elastomers, either alone or in combination.

[0064] When toughening agents are added, such components are present in an amount of less than 20 weight percent, based on the total weight of the thermoset resin matrix.

[0065] The thermosetting resin matrix may also include various flame retardants and smoke suppressants, for example, to impart specific flame retardant properties. Examples of such suppressants are metal oxides, alumina trihydrate (ATH), zinc borates, such as Firebrake® ZB (commercially available from USBorax Inc., Boron, California USA), ammonium polyphosphates, polyphosphazenes, phosphorus modified epoxies. When present, the amount of the above additives may be up to 35% by weight, based on the total weight of the resin matrix.

[0066] The reinforcing fibers of the composite layer may be in the form of chopped or continuous fibers, tows composed of multiple filaments, continuous unidirectional fibers, nonwoven mats / veils of randomly distributed fibers, woven fabrics or nonwoven fabrics. Nonwoven fabrics include non-crimped fabrics that contain unidirectional fibers held in place by stitches. As used herein, the term "unidirectional" means aligned parallel to the same direction.

[0067] Reinforcing fibers include carbon or graphite fibers, glass fibers, and fibers formed from silicon carbide, alumina, boron, quartz, and ceramics, as well as fibers formed from polymers such as, for example, polyolefins, poly(benzothiazoles), poly(benzimidazoles), polyarylates, poly(benzoxazoles), aromatic polyamides, polyaryl ethers, and the like, and may include mixtures having two or more such fibers. In some embodiments, the fibers are selected from glass fibers, carbon fibers, and aromatic polyamide fibers, such as those sold under the trademark KEVLAR.

[0068] Each composite layer may comprise 30% to 60%, or 35% to 50% by weight of a thermoplastic polymer or thermoset resin matrix, based on the total weight of the composite layer. The total area weight of each composite layer is less than 200 gsm (g / m 2 ) to 2000 gsm, and in some preferred embodiments, may range from 450 gsm to 600 gsm.

[0069] Manufacturing method The components of the multi-layer composite structures disclosed herein are assembled and consolidated by the application of heat and pressure to produce a bonded structure. Any conventional means for applying heat and pressure can be used, such as heated platens or heated rollers. In a preferred embodiment, consolidation of the multi-layer composite structure is carried out by passing the structure through a double belt press. Such consolidation while the multi-layer composite structure passes through the double belt press can be carried out at temperatures ranging from 200° C. to 260° C. for 1 to 10 minutes.

[0070] FIG. 2 shows an example of a continuous processor with a double belt press suitable for consolidating the foam core, adhesive film, and outer skin assembly to form an integrated panel. Referring to FIG. 2, the processor includes an upper endless belt 20, a lower endless belt 21, a number of heating elements 22 in a heating zone, a nip roll 23 for adjusting the distance, an S roll 24 for adjusting the final shape, a number of cooling elements 25 in a cooling zone, an edge trimmer 26 downstream of the cooling zone, an optional cross-sectional cutter 27, and an optional lamination mechanism 28. The endless belts rotate in opposite directions and their mutually facing sides are pressed against each other and against the material (M) passing between the belts. The heating and cooling elements are located adjacent to the parts of the belts that are in contact with the material passing between the belts. One advantage of this type of double belt press system is that the consolidation of the foam core sandwich structure can be performed at low pressure, e.g., less than 5 bar, thereby avoiding distortion or collapse of the foam core. The endless belts can be made of a non-sticky elastic material such as polytetrafluoroethylene (PTFE) or non-sticky stainless steel that is resistant to high temperatures. In a preferred example, a double belt press with non-sticky stainless steel belts is used to improve the finish of the sandwich surface.

[0071] In a preferred embodiment, the manufacture of the multi-layer composite structure is carried out in a continuous isovolumetric process, which comprises: (a) forming a multi-layer assembly having at least the following components: a thermoplastic foam core having two opposing surfaces, a thermoplastic adhesive film on one or both of the opposing surfaces of the thermoplastic foam core, one or more layers of fiber reinforced composite material in each thermoplastic adhesive film; (b) passing the assembly between two endless belts of a double belt press at a line speed of 0.5 to 5 m / min, wherein the distance between the endless belts is in the range of 3 mm to 40 mm and 1 mm to 10 mm lower than the combined thickness of the assembly in (a) before passing through the double belt press; (c) heating the sandwich structure while passing through the double belt press to a temperature in the range of 200°C to 260°C for 1 to 10 minutes.

[0072] The thermoplastic foam core, the thermoplastic adhesive film, and the composite layer are as described above.

[0073] The multi-layer assembly can be assembled just before the entrance to the double belt press by unwinding a continuous sheet of composite material from a feed roller and placing it on a conveyor. A further sheet of composite material can be fed by a further feed roller and placed on the previously laid sheet of composite material. A thermoplastic foam core in sheet form having an adhesive film thereon is then placed on the sheet of composite material such that the adhesive film is in contact with the sheet of composite material. One or more top sheets of composite material unwound from further feed rollers are placed on top of the foam core sheet to form a second outer skin of the composite material. In such a case, the foam core sheet has an adhesive film pre-applied to each of its upper and lower faces.

[0074] In one embodiment, the continuous isovolumetric process is equipped with a Roller Carpet Module (RCM) to finely distribute and control the thickness over the entire length and width of the material. The RCM includes several small rolls, both top and bottom, in contact with the continuous steel belt, which provides very uniform thickness control over the entire width of the steel belt. In another embodiment, the continuous isovolumetric process further includes a Calender Module (CAM) including top and bottom calender rolls that can apply stronger pressure to the steel belt to control the thickness of the material with high pressure resistance over the entire length and width of the material. In one preferred embodiment, the continuous isovolumetric process is applied by a machine equipped with a Roller Carpet Module (RCM) to better and precisely control the thickness of the foam and then the sandwich.

[0075] In another embodiment, the production of the multi-layer composite structure is carried out in a continuous isostatic process, the process comprising: (a) forming a multi-layer assembly as described above; (b) passing the assembly between two endless belts of a double belt press at a line speed of 0.5-5 m / min under a positive pressure of less than 5 bar, e.g. 1-2 bar; (c) heating the assembly to a temperature in the range of 200°C to 260°C for 1 to 10 minutes while passing through the double belt press. EXAMPLES

[0076] Example 1 Control panel with unreinforced thermoplastic skin by isovolumetric process A sandwich panel was constructed with a 17.5 mm thick Tegracore® foam core, two PPSU R-5100 resin film layers (each having a thickness of 63 μm) as top and bottom skins, and approximately 70 gsm of Bostik SPA145FR-A Sharnet® adhesive film between each skin and the foam core. Bostik SPA145FR-A Sharnet® is a flame retardant polyester web adhesive. Tegracore® has a strength of 53 Kg / m 3 The thermoplastic foam core is a PPSU-based closed cell thermoplastic foam core having a density of 1000:1.

[0077] The assembled panels were passed through a double-belt continuous machine having two opposing endless PTFE belts and a heating process zone of 12 linear meters. Bonding and consolidation of the assembled sandwich panels was carried out using a line speed of 1 m / min with the heating zone temperature set at 220°C. The distance between the two opposing endless belts was equal to 11.8 mm.

[0078] A cross-section of the resulting consolidated sandwich panel is shown in Figure 3, which is a finished image of the skin / core interface taken at 100x magnification in dark field light. The panel showed weak bond lines between the foam core and the PPSU outer skin layers, which peeled easily during the cutting operation.

[0079] The consolidated sandwich panel coupons were subjected to a Climb Drum Peeling test according to EN2243-3, tensioned at 25mm / min. The test results showed an average peel strength of less than 10N / 75mm.

[0080] Example 2 Panels with unreinforced thermoplastic skins by isovolumetric process Two sandwich panels were assembled as in Example 1, but using a 100 μm PSU resin film as an adhesive film between the foam core and each of the two PPSU skin layers.

[0081] Each sandwich panel was passed through the double belt continuous machine of Example 1, with the heating temperature set at 220° C. in one case and at 250° C. in the second case, using a line speed of 1 m / min in both cases. In both cases the distance between the two opposing endless belts was equal to 11.8 mm.

[0082] Both resulting consolidated sandwich panels showed good bonding between the thermoplastic film adhesive and the core as can be seen in Figure 4, which is a finished image of the core / skin interface taken at 100x magnification under dark field light.

[0083] The consolidated sandwich panel coupons were subjected to an ascending drum peel test according to EN2243-3 at a tension of 25 mm / min. The test results showed that the sandwiches produced at 220° C. had an average peel strength of 260 N / 75 mm and 344 N / 75 mm, respectively, for the sandwiches produced at 250° C. These values ​​are significantly greater than the peel strength values ​​obtained for the control sandwich panels of Example 1, in which Bostik SPA145FR-A Sharnet® polyester was used as the adhesive film.

[0084] Example 3 Panels with unreinforced thermoplastic skins by isostatic process Two sandwich panels similar to those described in Example 2 were assembled and passed through a double belt continuous machine having two opposing endless stainless steel belts and a heated process zone of 8 linear meters that applied an absolute pressure of 2 bar throughout the heated process zone of 8 linear meters followed by cooling.

[0085] The first panel was produced using a line speed of 1.5 m / min with the heating temperature set at 205° C. The second panel was produced using a line speed of 0.5 m / min with the heating temperature set at 230° C.

[0086] The resulting consolidated panel showed good bond lines between the foam core and the PPSU skin layers.

[0087] The consolidated sandwich panel coupons were subjected to an ascending drum peel test according to EN2243-3 at a tension of 25 mm / min. The test results showed that the sandwiches produced at 205°C and a line speed of 1.5 m / min had an average peel strength of 250 N / 75 mm, and the sandwiches produced at 230°C and a line speed of 0.5 m / min had an average peel strength of 260 N / 75 mm. These peel strength values ​​are significantly greater than those obtained with the control sandwich panels of Example 1.

[0088] Example 4 Panels with thermoset skins Sandwich panels were constructed having a Tegracore® foam core (12 mm thick), two thermoset skins, and a 100 μm PSU resin film between each thermoset skin and the foam core. Each thermoset skin had two layers of MTM348FR-7781-38%RC on each side, which is a prepreg supplied by Solvay with a resin content of 38% by weight and containing MTM348FR flame retardant epoxy resin system and 7781E glass fabric.

[0089] The assembled sandwich panels were passed through the double belt continuous machine of Example 1 using a heating temperature set at 175° C. and a line speed of 0.5 m / min. The aforementioned temperature and time resulted in complete cure of the thermoset skin.

[0090] The resulting cured sandwich panel showed good bond lines between the thermoset skins and the thermoplastic film adhesive as well as good bonds between the thermoplastic film adhesive and the foam core.

[0091] The consolidated sandwich panel coupons were subjected to an ascending drum peel test according to EN2243-3 at a tension of 25 mm / min. The test results showed an average peel strength of 314 N / 75 mm.

[0092] Example 5 Sandwich panels with thermoplastic skins reinforced with glass fabric by isovolumetric process The sandwich panels were constructed from a Tegracore® foam core (12 mm thick), two fiber-reinforced thermoplastic skins, and a 100 μm PSU adhesive film between each thermoplastic skin and the foam core. As a continuous sheet, each thermoplastic skin was produced by pressing a continuous 7781e-glass fabric into a continuous PPSU polymer film layer so that the fabric was embedded in the polymer layer. The polymer content of each thermoplastic skin is approximately 40% by weight.

[0093] To consolidate the sandwich panels, a double-belt continuous machine was used as disclosed in Example 1. The heating temperature was set at 250° C., the line speed was 1 m / min, and the distance between the opposing endless belts was 12.5 mm.

[0094] The resulting consolidated panel showed good bond lines between the fiber reinforced thermoplastic skins and the adhesive film, and good bonding between the adhesive film and the foam core.

[0095] The consolidated sandwich panel coupons were subjected to an ascending drum peel test according to EN2243-3 at a tension of 25 mm / min. The test results showed an average peel strength of 408 N / 75 mm.

[0096] Example 6 Glass fabric reinforced thermoplastic skin sandwiches by isovolumetric process. Sandwich panels similar to those in Example 5 were constructed, but consolidation was performed by passing the assembled panels through a machine equipped with a roller carpet module (RCM) to control the foam and sandwich thickness over the entire length and width of the material. A temperature of 250°C was used to simultaneously obtain good impregnation of the glass fabric and good adhesion of the PPSU-based skin to the adjacent PSU adhesive film.

[0097] The consolidated sandwich panel coupons were subjected to an ascending drum peel test according to EN2243-3 at a tension of 25 mm / min. The test results showed an average peel strength of 360 N / 75 mm.

Claims

1. a thermoplastic foam core having two opposing surfaces; a thermoplastic adhesive film on at least one of the opposing surfaces of the thermoplastic foam core; a first composite layer adhered to the thermoplastic adhesive film; A sandwich structure comprising: Where: the first composite layer comprises reinforcing fibers embedded in a polymer or resin matrix; The thermoplastic foam core has a glass transition temperature (T) of 210° C. to 240° C. as determined by differential scanning calorimetry (DSC) at a heating rate of 5° C. / min. g ), said formed thermoplastic material being formed from a foamable composition comprising one or more poly(aryl ether sulfone) (PAES) polymers; The thermoplastic adhesive film is formed from a polymer composition comprising at least 80 wt. % of one or more polysulfones, based on a total weight of the polymer composition, the one or more polysulfones being capable of achieving a T of the foamed thermoplastic material as determined by DSC at a heating rate of 5° C. / min. g T at least 20° C. lower than g A sandwich structure having

2. The foamed thermoplastic material is formed from a foamable composition comprising at least 80 weight percent PPSU polymer, based on the total weight of the composition, the PPSU polymer comprising at least 50 mole percent repeat units (R PPSU ), said mole percent being based on the total moles of said polymer: 【Chemistry 1】 10. The sandwich structure of claim 1, wherein the PPSU polymer has a weight average molecular weight (Mw) in the range of 30,000 to 90,000 g / mol as determined by gel permeation chromatography (GPC).

3. The polysulfone (PSU) in the polymer composition of the thermoplastic adhesive film is at least 50 mol % of the following formula (U): 【Chemistry 2】 (R PSU ) repeat units, the mole percentage being based on the total moles of repeat units in the polymer, and the PSU has a weight average molecular weight (M) in the range of 30,000 to 110,000 g / mole, as determined by gel permeation chromatography (GPC). w 3. The sandwich structure according to claim 1 or 2, comprising:

4. 4. The sandwich structure of claim 1, wherein the first composite layer comprises reinforcing fibers embedded in a thermoplastic polymer matrix comprising one or more thermoplastic polymers selected from polyethersulfone (PES), polyetherethersulfone (PEES), polyphenylsulfone, polyphenylene sulfide (PPS), polysulfone, poly(arylethersulfone) polymers, polyphenylsulfone (PPSU), polyester, polyimide, polyetherimide (PEI), polyetherketoneketone (PEKK), polyetheretherketone (PEEK), polyaryletherketone (PAEK) polymers, polyetherketoneketone (PEKK), polyketone, polyamide, polyphthalamide, polymethacrylate, polyurethane, polyarylether, polyarylsulfide, polyphenylene, polyphenylene oxide (PPO), and copolymers thereof.

5. 4. The sandwich structure of claim 1, wherein the first composite layer comprises reinforcing fibers embedded in a curable resin matrix comprising one or more epoxy resins and at least one hardener.

6. 6. The sandwich structure of claim 1, wherein the reinforcing fibers of the first composite layer are in the form of continuous unidirectional fibers, chopped fibers, a woven fabric, or a non-woven mat or veil of randomly arranged fibers.

7. 7. The sandwich structure of claim 1, wherein the reinforcing fibers of the first composite layer are selected from carbon fibers, glass fibers, polymeric fibers, fibers formed from silicon carbide, alumina, boron, or quartz, and combinations thereof.

8. 8. A sandwich structure according to any one of claims 1 to 7, further comprising one or more further composite layers on the first composite layer, each further composite layer comprising reinforcing fibres embedded in a polymer or resin matrix.

9. A sandwich structure according to any one of claims 1 to 8, wherein the thermoplastic foam core is free of any reinforcing fibres or openings spanning its thickness.

10. The foam core has a compressibility of 45 kg / m as measured by ASTM D1622. 3 ~150kg / m 3 10. The sandwich structure according to claim 1, having a density in the range of

11. 11. The sandwich structure according to any one of claims 1 to 10, wherein the foam core has a thickness in the range of 3 mm to 30 mm and the adhesive film has a thickness in the range of 25 to 250 microns (μm).

12. A sandwich structure as claimed in any one of the preceding claims, wherein the first composite layer has an areal weight in the range of 200 to 2000 gsm.

13. 1. A continuous method for assembling a sandwich structure, comprising: (a) forming a multi-layer assembly having at least the following components: A thermoplastic foam core having two opposing surfaces, a thermoplastic adhesive film on one or both of the opposing surfaces of the thermoplastic foam core, and one or more layers of fiber reinforced composite material in the / each thermoplastic adhesive film, wherein the thermoplastic foam core has a glass transition temperature (T g ) and the / each thermoplastic adhesive film is formed from a foamed thermoplastic material having a T of the foamed thermoplastic material. g T at least 20° C. lower than g The thermoplastic polymer composition includes one or more polysulfones (PSU) having a T g is determined by differential scanning calorimetry (DSC) at a heating rate of 5° C. / min, and the foamed thermoplastic material is formed from a foamable composition comprising one or more poly(aryl ether sulfone) (PAES) polymers. (b) passing the multi-layer assembly between two endless belts of a double belt press; and (e) heating the sandwich structure during passage through the double belt press to a temperature of 200° C. to 260° C. for a period of 1 to 10 minutes. A method comprising:

14. The method according to claim 13, wherein step (b) is carried out under a positive pressure exerted by said endless belt of less than 5 bar and at a line speed of 0.5 to 5 m / min.

15. 14. The method according to claim 13, wherein step (b) is carried out at a line speed of 0.5 to 5 m / min, the distance between said endless belts being in the range of 3 mm to 40 mm, said distance between said endless belts being 1 mm to 10 mm less than the total thickness of the multi-layer assembly in (a).

16. The foamed thermoplastic material is formed from a foamable composition comprising at least 80 weight percent PPSU polymer, based on the total weight of the composition, the PPSU polymer comprising at least 50 mole percent repeat units (R PPSU ), said mole percent being based on the total moles of said polymer: 【Chemistry 3】 16. The method of any one of claims 13 to 15, wherein the PPSU polymer has a weight average molecular weight (Mw) in the range of 30,000 to 90,000 g / mol, as determined by gel permeation chromatography (GPC).

17. The PSU in the composition of the thermoplastic adhesive film has a T of less than 200° C., as determined by DSC at a heating rate of 5° C. / min. g The method according to any one of claims 13 to 16, comprising:

18. The PSU in the composition of the thermoplastic adhesive film is at least 50 mol % of the following formula (U): 【Chemistry 4】 Repeating units (R PSU ), the mole percentage being based on the total moles of repeat units in the polymer, and the PSU has a weight average molecular weight (M) in the range of 30,000 to 110,000 g / mole, as determined by gel permeation chromatography (GPC). w 20. The method of claim 17, comprising the steps of:

19. The fiber reinforced composite material has a T in the range of 210° C. to 240° C. as determined by DSC at a heating rate of 5° C. / min. g The method of any one of claims 13 to 18, comprising reinforcing fibers embedded in a thermoplastic polymer matrix comprising an amorphous thermoplastic material having

20. 19. The method of any one of claims 13 to 18, wherein the fiber reinforced composite material comprises reinforcing fibers embedded in a thermoplastic polymer matrix comprising one or more thermoplastic polymers selected from polyethersulfone (PES), polyetherethersulfone (PEES), polyphenylsulfone, polyphenylene sulfide (PPS), polysulfone, poly(arylethersulfone) polymers, polyphenylsulfone (PPSU), polyester, polyimide, polyetherimide (PEI), polyetherketoneketone (PEKK), polyetheretherketone (PEEK), polyaryletherketone (PAEK) polymers, polyetherketoneketone (PEKK), polyketone, polyamide, polyphthalamide, polymethacrylate, polyurethane, polyarylether, polyarylsulfide, polyphenylene, polyphenylene oxide (PPO), and copolymers thereof.

21. 19. The method of any one of claims 13 to 18, wherein the fiber reinforced composite material comprises reinforcing fibers embedded in a curable resin matrix comprising one or more epoxy resins and at least one hardener.

22. 22. The method of any one of claims 19 to 21, wherein the reinforcing fibers are selected from carbon fibers, glass fibers, polymeric fibers, fibers formed from silicon carbide, alumina, boron, quartz, and combinations thereof.

23. The foam core has a compressibility of 45 kg / m as measured by ASTM D1622. 3 ~150kg / m 3 The method according to any one of claims 13 to 22, having a density in the range of

24. A method according to any one of claims 13 to 23, wherein the foam core has a thickness in the range of 3mm to 30mm.

25. A method according to any one of claims 13 to 24, wherein the / each adhesive film has a thickness in the range 25 to 250 microns (μm).

26. A method as claimed in any one of claims 13 to 25, wherein the / each layer of fibre reinforced composite material has an areal weight in the range 200 to 2000gsm.

27. The method according to any one of claims 13 to 26, wherein the endless belt is made from an elastic material or stainless steel.

Citation Information

Patent Citations

  • Foamable laminated board for expansion molding

    JP1993212821A

  • Frp automobile panel and its manufacturing method

    JP2003146252A

  • Polyetherimide / Poly(biphenyl ethersulfone) foam

    JP2014532108A

  • Fiber reinforced composite material layer

    JP2019006037A

  • Multilayer panel

    US5087500A